2016
DOI: 10.3389/fmicb.2016.01704
|View full text |Cite
|
Sign up to set email alerts
|

“Candidatus Gortzia shahrazadis”, a Novel Endosymbiont of Paramecium multimicronucleatum and a Revision of the Biogeographical Distribution of Holospora-Like Bacteria

Abstract: Holospora spp. and “Candidatus Gortzia infectiva”, known as Holospora-like bacteria (HLB), are commonly found as nuclear endosymbionts of ciliates, especially the Paramecium genus. HLB are related by phylogenetic relationships, morphological features, and life-cycles, which involve two alternating morphotypes: reproductive and infectious forms (RF, IF). In this paper we describe a novel species belonging to the “Ca. Gortzia” genus, detected in P. multimicronucleatum, a ciliate for which infection by an HLB has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 78 publications
1
41
0
Order By: Relevance
“…chlorelligerum occupies basal position, thus forming a separate lineage. “ Candidatus Gortzia infectiva”, an Holospora -like bacterium, is confirmed as the closest relative of Holospora genus [23, 99]. …”
Section: Discussionmentioning
confidence: 99%
“…chlorelligerum occupies basal position, thus forming a separate lineage. “ Candidatus Gortzia infectiva”, an Holospora -like bacterium, is confirmed as the closest relative of Holospora genus [23, 99]. …”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of the distribution of Holospora species including H. caryophila (Serra et al, 2016), the authors list the countries with positive reports: Austria, Czech Republic, Germany, Italy, Russia, Ukraine, and USA. The here employed naïve P. biaurelia strains derive from different European regions as well as countries in Asia and Australia (Table 1), thus they do not overlap with the known incidence of H. caryophila (with the exception of Russia).…”
Section: Discussionmentioning
confidence: 99%
“…Boscaro et al recently have reported a new genus of HLB, Candidatus Gortzia, which is evidently a sister taxon to the genus Holospora (Boscaro et al 2013). The genus currently includes two species, Сandidatus Gortzia infectiva (Boscaro et al 2013), and Сandidatus G. shahrazadis (Serra et al 2016), macronuclear symbionts of P. jenningsi and P. multimicronucleatum, respectively. The sequences of their 16S rRNA gene differ by 9.1-9.7% from the 16S rRNA of Holospora species.…”
Section: Introductionmentioning
confidence: 99%